The population genetics of sporophytic self-incompatibility in Senecio squalidus L. (Asteraceae) I: S allele diversity in a natural population. - Brennan, A; Harris, S; Tabah, D; Hiscock, S (2002)
Twenty-six individuals of the sporophytic self-incompatible (SSI) weed, Senecio squalidus were crossed in a full diallel to determine the number and frequency of S alleles in an Oxford population. Incompatibility phenotypes were determined by fruit-set results and the mating patterns observed fitted a SSI model that allowed us to identify six S alleles. Standard population S allele number estimators were modified to deal with S allele data from a species with SSI. These modified estimators predicted a total number of approximately six S alleles for the entire Oxford population of S. squalidus. This estimate of S allele number is low compared to other estimates of S allele diversity in species with SSI. Low S allele diversity in S. squalidus is expected to have arisen as a consequence of a disturbed population history since its introduction and subsequent colonisation of the British Isles. Other features of the SSI system in S. squalidus were also investigated: (a) the strength of self-incompatibility response; (b) the nature of S allele dominance interactions; and (c) the relative frequencies of S phenotypes. These are discussed in view of the low S allele diversity estimates and the known population history of S. squalidus.